Cardiogenic oscillation induced ventilator autotriggering - Kaloria, Narender; Gupta, Akhilesh; Goila, Ajay; Sood, Rajesh (Journal of Neuroanaesthesiology and Critical Care, 2015)
Cardiogenic oscillation during mechanical ventilation can auto-trigger the ventilator resembling patient initiated breadth. This gives a false sense of intact respiratory drive and determination brain death, even if other tests are positive, is not appropriate in such a situation. It will prolong the ICU stay and confound the brain-death determination. In this case report, we describe a 35 year old man who was brought to the hospital after many hours of critical delay following multiple gun shot injuries. The patient suffered a cardiac arrest while on the way from another hospital. After an emergency laparotomy, patient was shifted to Intensive Care Unit (ICU) with Glasgow Coma Scale (GCS) score of E1VTM1 and was mechanically ventilated. Despite absence of brainstem reflexes, the ventilator continued to be triggered on continuous positive airway pressure (CPAP) mode and the patient maintained normal oxygen saturation and acceptable levels of carbon dioxide. An apnoea test confirmed absent respiratory drive. Ventilatory waveform graph analysis, revealed cardiogenic oscillation as the cause for autotrigerring.
Keywords: Autotriggering; cardiogenic oscillation; ventilator